Unfavourable results following reduction mammoplasty - Lakshmi Saleem; Jerry R. John (Indian Journal of Plastic Surgery)
Breast reduction is a common cosmetic surgical procedure. It aims not only at bringing down the size of the breast proportionate to the build of the individual, but also to overcome the discomfort caused by massive, ill-shaped and hanging breasts. The operative procedure has evolved from mere reduction of breast mass to enhanced aesthetic appeal with a minimum of scar load. The selection of technique needs to be individualised. Bilateral breast reduction is done most often. Haematoma, seroma, fat necrosis, skin loss, nipple loss and unsightly, painful scars can be the complications of any procedure on the breast. These may result from errors in judgement, wrong surgical plan and imprecise execution of the plan. Though a surfeit of studies are available on breast reduction, very few dwell upon its complications. The following article is a distillation of three decades of experience of the senior author (L.S.) in reduction mammoplasty. An effort is made to understand the reasons for unfavourable results. To conclude, most complications can be overcome with proper selection of procedure for the given patient and with gentle tissue handling.